2012
DOI: 10.1021/ac3011473
|View full text |Cite
|
Sign up to set email alerts
|

Optical Aptasensors for the Analysis of the Vascular Endothelial Growth Factor (VEGF)

Abstract: The vascular endothelial growth factor, VEGF, is an important biomarker for different diseases and clinical disorders. We present a series of optical aptasensor-based sensing platforms for VEGF that include the following: (i) A FRET-based sensor that involves the VEGF-induced separation of aptamer-functionalized quantum dots blocked by a quencher nucleic acid (detection limit 1 nM). (ii) A FRET-based sensor based on the VEGF-induced assembly of the aptamer subunits functionalized with QDs and a dye acceptor (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
154
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 179 publications
(157 citation statements)
references
References 50 publications
3
154
0
Order By: Relevance
“…A comparison of the conditions determined in this work with those reported previously demonstrated that the optimization of the composition of the substrate solution significantly improved the sensitivity of the CL determination of PMDNAzyme. Because PMDNAzyme is already used in the construction of assays for determination of DNA and proteins [45][46][47], the obtained results open up promising perspectives for using the proposed method to improve the sensitivity of PMDNAzyme-based assays and the production of commercial kits. 1% DMSO, and 0.05% Triton X-100, and then luminol and H 2 O 2 were added up to 1 and 50 mM, respectively [28]; for solution 3, PMDNAzyme was prepared at an interaction of EAD2 aptamer (1 lM) and hemin (0.5 lM) in 25 mM Hepes buffer (pH 7.4) with 20 mM KCl, 200 mM NaCl, 1% DMSO, and 0.05% Triton X-100, and then luminol and H 2 O 2 were added up to 0.5 and 30 mM, respectively [22,23]; for solution 4, PMDNAzyme was prepared at an interaction of EAD2 aptamer (1 lM) and hemin (0.5 lM) in 25 mM Hepes buffer (pH 9.0) with 20 mM KCl, 200 mM NaCl, 1% DMSO, and 0.05% Triton X-100, and then luminol and H 2 O 2 were added up to 50 lM and 10 mM, respectively [24].…”
Section: Discussionmentioning
confidence: 97%
“…A comparison of the conditions determined in this work with those reported previously demonstrated that the optimization of the composition of the substrate solution significantly improved the sensitivity of the CL determination of PMDNAzyme. Because PMDNAzyme is already used in the construction of assays for determination of DNA and proteins [45][46][47], the obtained results open up promising perspectives for using the proposed method to improve the sensitivity of PMDNAzyme-based assays and the production of commercial kits. 1% DMSO, and 0.05% Triton X-100, and then luminol and H 2 O 2 were added up to 1 and 50 mM, respectively [28]; for solution 3, PMDNAzyme was prepared at an interaction of EAD2 aptamer (1 lM) and hemin (0.5 lM) in 25 mM Hepes buffer (pH 7.4) with 20 mM KCl, 200 mM NaCl, 1% DMSO, and 0.05% Triton X-100, and then luminol and H 2 O 2 were added up to 0.5 and 30 mM, respectively [22,23]; for solution 4, PMDNAzyme was prepared at an interaction of EAD2 aptamer (1 lM) and hemin (0.5 lM) in 25 mM Hepes buffer (pH 9.0) with 20 mM KCl, 200 mM NaCl, 1% DMSO, and 0.05% Triton X-100, and then luminol and H 2 O 2 were added up to 50 lM and 10 mM, respectively [24].…”
Section: Discussionmentioning
confidence: 97%
“…When compared with other transduction methods based on FRET (12 nM) and chemiluminescence (2.6 nM), detection of VEGF via CRET offered an improved LOD (875 pM). 146 Chemiluminescence. In addition to serving as CRET acceptors, QDs can directly participate in CL reactions as the emitter.…”
Section: Bioanalysis and Bioimaging With Quantum Dotsmentioning
confidence: 99%
“…However, many detection strategies are based on the use of enzymes to selectively dissociate the aptamer/target complex while releasing an active marker (redox group, fluorophore, etc), leading to the release of the target to perform a new cycle (complexation/release). For example, the use of a shorter sequence, functionalized at one end by a quantum dot (QD) and the other by a quencher, shows no fluorescence (FRET between the quencher and the QD, Freeman et al 2012). In the presence of the target (VEGF) and the addition of a short template sequence, the aptamer conformation switches to a G-quartet structure in the presence of the target, activating one of the sequence positions towards exonuclease.…”
Section: Target Recyclingmentioning
confidence: 99%